Method for improving alkali impregnation yield of fiber raw material

By gently dry heat treatment of the fiber raw materials, the reactive groups are activated and the radical condensation reaction is initiated, the problem of low pulping yield during the pre-impregnation of the fiber raw materials is solved, and the effect of improving the alkali impregnation yield and reducing the pulping cost is achieved.

CN119640606AActive Publication Date: 2025-03-18INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510007581.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-18
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The prior art has the problem of low pulping yield in the pre-impregnation process of fiber raw materials, which leads to an increase in chemical consumption and an increase in the pollution load of pulping wastewater.

Method used

By performing a short and relatively mild dry heat treatment on the fiber raw materials, the reactive groups in the cellulose, hemicellulose and lignin precursors are activated to form free radicals, and a radical condensation reaction is initiated during the cooling process to establish a stable connection between the precursor and the main structure of the fiber raw material.

Benefits of technology

It improves the alkali impregnation yield of fiber raw materials, reduces mass loss during the pre-impregnation process, reduces pulping costs, and reduces pollutant emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640606A_ABST
    Figure CN119640606A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the alkali impregnation yield of a fiber raw material, which comprises the following steps: screening the fiber raw material to obtain qualified wood chips, and before alkali impregnation, carrying out at least one dry heat treatment on the washed and dehydrated fiber raw material at 105-130 DEG C for 10-60 minutes. According to the method disclosed by the invention, under the condition of no chemical modification, only relatively mild heat treatment is used, and precursor micromolecules originally located in a cell cavity are stably connected with a main body structure of a fiber raw material as far as possible through free radical condensation, so that the alkali impregnation yield of pulping of the chemimechanical pulp is improved; and the pulping cost is saved while the subsequent paper pulp performance is ensured, and the emission of pollutants is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of pulping technology, and in particular to a pretreatment method for improving the alkali impregnation yield of fiber raw materials by utilizing heat treatment. Background Art

[0003] With the continuous increase in the production capacity of chemical-mechanical pulp, the domestic wood resources are in short supply. Large-scale chemical-mechanical pulp production lines are difficult to ensure a stable supply of fiber raw materials, and have to use a large amount of young wood, branch wood, small-diameter wood and processing residues. These raw materials are still in the growth stage of their life cycle. When life activities stop, they contain a large amount of lignin precursors (small molecular weight water-soluble phenylpropane structural monomers and polymers) and hemicellulose and cellulose precursors (small molecular weight water-soluble polysaccharides and monosaccharide molecules) in the plant cell cavity. (Jiao Ting, Zhu Beiping, Guo Wenliang, et al. Study on the antioxidant properties of hot water extracts of three kinds of wood fiber raw materials [J]. Journal of the Chinese Society of Pulp and Paper, 2024, 39(03): 63-70). These precursors are rich in active groups, have a small molecular weight, and are relatively unstable in structure. In the pulping process, they not only increase the consumption of chemicals, but also increase the pollution load of pulping wastewater.

[0004] Pre-impregnation is a key step in the chemical mechanical pulping process. Its mechanism is to use the nucleophilicity of hydroxide to moderately destroy various connecting bonds in the fiber raw materials to achieve the purpose of swelling and softening the fiber raw materials. Otherwise, the fiber raw materials that are too hard will have more cutting effects during the subsequent disc grinding process, affecting the strength of the subsequent pulp. In the pre-impregnation process, the pulping yield will inevitably be lost. The pre-impregnation extract mainly includes the various small molecule precursors originally contained in the raw materials mentioned above, as well as the water-soluble small molecules formed after the relatively unstable lignin structure reacts with sodium hydroxide. At present, the pulping yield is mainly improved by reducing the amount of chemicals used in alkali pre-impregnation, but due to the limitations of the pulp strength index in subsequent processes, the adjustment range of the amount of chemicals is limited. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a pretreatment method for improving the alkali impregnation yield of fiber raw materials by heat treatment in view of the shortcomings of the prior art.

[0006] The various connecting bonds existing in the fiber raw materials are mainly carbon-carbon bonds and carbon-oxygen ether bonds, both of which can be synthesized by free radical condensation reactions. If the main structure of the fiber raw material (lignin, cellulose and hemicellulose) and various precursor small molecules can be excited into free radicals by mild heat treatment, and connected to the main structure of the fiber raw material by free radical condensation reaction during the cooling process, the originally water-soluble small molecules can be stably connected to the main structure of the fiber raw material, reducing the mass loss of the pre-impregnation treatment process and improving the pulping yield. Based on this principle, the present invention activates various groups or active sites with strong reaction activity in the extract (cellulose, hemicellulose and lignin precursors) and the main structure of the fiber raw material by performing a short-term and relatively mild heat treatment on the slurry, so that it forms free radicals, and triggers free radical condensation reactions during the cooling process. The condensation reaction establishes the connecting bonds between various precursor small molecules and the main structure of the fiber raw material, making these originally water-soluble small molecules difficult to dissolve, thereby achieving the purpose of increasing the pulping yield, thereby reducing the pulping cost and increasing corporate profits.

[0007] In order to solve the above technical problems, the present invention discloses a method for improving the alkali impregnation yield of fiber raw materials, characterized in that after washing and dehydrating the fiber raw materials, before alkali impregnation, the washed and dehydrated fiber raw materials are subjected to at least one dry heat treatment, the treatment temperature is 105°C to 130°C, and the total treatment time is 10min to 60min. The heat treatment temperature is very important for the alkali treatment yield, the subsequent refining energy consumption and the pulp uniformity, because the glass transition temperature of the lignin structure is about 135°C. Exceeding this temperature will cause the lignin in the fiber raw materials to become a liquid fluid, which may be over-enriched in some parts. After the heat treatment is completed, the temperature will be lower than 135°C, which will re-condense, resulting in excessive thickness of the outer layer lignin of some microfibrils of the fiber raw materials, which will increase the subsequent refining energy consumption and affect the uniformity of the pulp force. At the same time, the degree of heat treatment cannot be excessive. If too many free radical polycondensation reactions are triggered, the fiber raw materials will be carbonized or even burned, and qualified pulp cannot be prepared. Due to the large structural differences of the fiber raw materials, the optimal value of the heat treatment degree of each raw material needs to be designed and optimized. Generally speaking, the slurry yield before and after heat treatment (i.e., the ratio of the mass difference after heat treatment to the original mass, because the polycondensation reaction occurs in an air atmosphere, the free radical polycondensation reaction mostly forms ether bonds, so the mass change is a positive value) is controlled not to be higher than 105%.

[0008] Wherein, the dry heat treatment is any one or a combination of hot air drying, baking and infrared heat treatment.

[0009] Preferably, the washed and dehydrated fiber raw material is subjected to several dry heat treatments, and the material is taken out after each treatment for 5 to 8 minutes, and then stirred evenly before the next dry heat treatment.

[0010] The fiber raw material is any one or more of eucalyptus, poplar, acacia, pine and bamboo.

[0011] In one embodiment, the alkali impregnation step is: alkali impregnating the dry heat pretreated pulp at a pulp concentration of 20% based on the condition, the amount of sodium hydroxide used is 30kg / t of absolute dry pulp, the reaction temperature is 95°C, and the reaction time is 1h.

[0012] The above-mentioned alkali impregnation treatment, subsequent pulping treatment and papermaking steps are all conventional natural chemical mechanical pulping processes. The process parameters will be different depending on the raw material structure. This method only lists conventional operations.

[0013] The present invention further proposes a papermaking method, characterized in that it comprises the following steps:

[0014] (1) Screening, washing and dehydrating the fiber raw materials;

[0015] (2) subjecting the raw material obtained in step (1) to at least one dry heat treatment at a temperature of 105° C. to 130° C. and a total treatment time of 10 min to 60 min;

[0016] (3) the fiber raw material obtained in step (2) is subjected to alkali impregnation treatment, the treatment conditions being: the slurry after dry heat pretreatment is subjected to alkali impregnation at a slurry concentration of 20% based on absolute dry pulp, the amount of sodium hydroxide used is 30 kg / t absolute dry pulp, the reaction temperature is 95° C., and the reaction time is 1 h;

[0017] (4) The slurry obtained after the alkali impregnation treatment in step (3) is ground to a Canadian freeness of 550 mL CSF using a high-consistency disc mill at a concentration of 20% to obtain a coarse pulp, and the coarse pulp is subjected to a secondary alkali treatment at a pulp concentration of 20%, with a sodium hydroxide dosage of 50 kg / t, a reaction temperature of 95° C., and a reaction time of 1 h. After the reaction is completed, the dissolution is washed and subjected to a medium-consistency disc mill at a pulp concentration of 10% to grind it to a Canadian freeness of about 300 mL CSF to obtain a fine pulp;

[0018] (5) After washing the fine pulp obtained in step (4), papermaking is carried out.

[0019] 7. The papermaking method according to claim 6, characterized in that in step (2), the dry heat treatment is any one of hot air drying, baking and infrared heat treatment or a combination of several of them.

[0020] 8. The papermaking method according to claim 6, characterized in that in step (2), the fiber raw material after washing and dehydration is subjected to dry heat treatment several times, and the material is taken out after each treatment for 5 minutes to 8 minutes, and then stirred evenly before the next dry heat treatment.

[0021] 9. The papermaking method according to claim 6, characterized in that in step (2), the fiber raw material is any one or more of eucalyptus, poplar, acacia, pine and bamboo.

[0022] Beneficial effects: The method of the present invention uses only relatively mild heat treatment without chemical modification, and tries to establish a stable connection between the precursor-like small molecules originally in the cell cavity and the main structure of the fiber raw material through free radical condensation, thereby improving the alkaline impregnation yield of the pulp, ensuring the subsequent pulp performance while saving pulping costs and reducing pollutant emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0024] Figure 1 The temperature optimization curve of pulping yield of green bamboo after hydrothermal pretreatment for 30 minutes (Comparative Example 1);

[0025] Figure 2 This is the time optimization curve of pulping yield of black poplar when it is pretreated with hot air at 110°C (Comparative Example 2);

[0026] Figure 3 The temperature and time optimization curve of pulping yield of Acacia mangium during hot air pretreatment (Example 1);

[0027] Figure 4 The temperature and time optimization curve of pulping yield of Eucalyptus grandis during baking pretreatment (Example 2);

[0028] Figure 5 The temperature and time optimization curve for pulping yield of black poplar during infrared heat treatment (Example 3);

[0029] Figure 6 The temperature and time optimization curve for pulping yield of green bamboo during baking pretreatment (Example 4);

[0030] Figure 7 This is the temperature and time optimization curve for pulping yield of larch during hot air pretreatment (Example 5). DETAILED DESCRIPTION

[0031] A method for improving the pulping yield of chemical mechanical pulp by dry heat pretreatment comprises the following steps:

[0032] (1) Pretreatment of fiber raw materials (including but not limited to eucalyptus, poplar, acacia, pine, bamboo and other chemical mechanical pulp raw materials): the fiber raw materials are screened, washed and dehydrated.

[0033] (2) Dry heat treatment of fiber raw materials: Dry heat pretreatment methods include but are not limited to hot air drying, baking and infrared heat treatment. The pretreatment process can be carried out in multiple steps, and one heat treatment method can be used alone or in combination. The heat treatment temperature is 105°C to 130°C, and the reaction time is 10 min to 60 min.

[0034] (3) Alkali impregnation treatment of fiber raw materials: The pulp after dry heat pretreatment was alkali impregnated at a pulp concentration of 20% (based on absolute dry pulp, the same below), the amount of sodium hydroxide was 30 kg / t odt pulp (kg / t absolute dry pulp, the unit of chemical dosage is referred to as kg / t below), the reaction temperature was 95°C, and the reaction time was 1 hour. After the reaction was completed, the dissolved matter was washed and the pulp yield A was calculated after the reaction was completed.

[0035]

[0036] Wherein, M1 is the absolute dry weight of the material after pre-impregnation, g; M0 is the absolute dry weight of the material before pre-impregnation, g.

[0037] (4) Subsequent treatment of chemical mechanical pulping of fiber raw materials: The pulp after alkali pre-impregnation is ground to a Canadian freeness of about 550 mL CSF using a high-consistency disc mill at 20% to obtain a coarse pulp. The coarse pulp is subjected to a secondary alkali treatment at a pulp concentration of 20%, with a sodium hydroxide dosage of 50 kg / t, a reaction temperature of 95°C, and a reaction time of 1 h. After the reaction is completed, the eluted material is washed and subjected to a medium-consistency disc mill at a pulp concentration of 10% to grind it to a Canadian freeness of about 300 mL CSF to obtain a fine pulp.

[0038] (5) Papermaking and performance testing:

[0039] After the obtained fine pulp is washed, papermaking and tensile strength testing are carried out.

[0040] Papermaking: According to GB7981-1999 Pulp Laboratory Paper Preparation Conventional Paper Forming Method;

[0041] Basis weight: According to GB / T 451.2-2002: Determination of basis weight of paper and paperboard;

[0042] Tensile strength: according to GB / T 12914-2002: Determination of tensile strength of paper and paperboard (constant rate of tension method).

[0043] In the above method, steps (3), (4) and (5) are all conventional natural chemical mechanical pulping processes. Depending on the raw material structure, the process parameters will vary. This method only lists conventional operations.

[0044] The beneficial effects of the present invention are described below through specific embodiments.

[0045] Example 1

[0046] Acacia mangium was used as the raw material, and after being processed by a chipper, it was screened to obtain qualified wood chips with a length of 50mm-100mm, a width of 2.5mm-10mm, and a thickness of 4.5mm-6mm. After washing and dehydrating the wood chips, they were dried with hot air at 120℃ for 30min. The material was taken out after every 5min of treatment, stirred evenly, and then sent to a hot air blower for drying. The final heat treatment yield was 103.76%. The obtained material was pre-impregnated (the slurry after dry heat pretreatment was alkaline impregnated at a pulp concentration of 20% (based on absolute dry pulp), the amount of sodium hydroxide was 30kg / t, the reaction temperature was 95℃, and the reaction time was 1h). The pulp treated with alkali impregnation was ground to a Canadian freeness of 550 mL CSF using a high-concentration disc mill at 20% to obtain a coarse pulp. The coarse pulp was subjected to a secondary alkali treatment at a pulp concentration of 20% (sodium hydroxide dosage of 50 kg / t, reaction temperature of 95°C, reaction time of 1 h), and the material yield was 88.80%. After the reaction, the dissolution was washed and subjected to a medium-concentration disc mill at a pulp concentration of 10% to grind it to a Canadian freeness of about 300 mL CSF to obtain a fine pulp. After the fine pulp was washed, it was used for papermaking, and the tensile strength of the obtained hand sheet was 0.69 kN / m. The raw material that was not treated with hot air drying had an alkali treatment yield of 85.72% and a tensile strength of 0.68 kN / m, an increase of 3.59% in yield, and almost no change in strength.

[0047] Example 2

[0048] Eucalyptus grandis was used as the raw material, and after being processed by a chipper, it was passed through a wood chip screen to obtain qualified wood chips with a length of 50mm to 100mm, a width of 2.5mm to 10mm, and a thickness of 4.5mm to 6mm. After the wood chips were washed and dehydrated, they were baked at 110℃ for 50min, wherein the material was taken out after each 5min treatment, stirred evenly, and then continued to be sent into the oven, and the final heat treatment yield was 102.12%. The obtained material was pre-impregnated with alkali (the slurry after dry heat pretreatment was alkali impregnated at a pulp concentration of 20% (based on absolute dry pulp), the amount of sodium hydroxide was 30kg / t, the reaction temperature was 95℃, and the reaction time was 1h). The slurry after alkali impregnation was ground to a Canadian freeness of 550mL CSF using a high-concentration disc mill at 20% to obtain a coarse pulp, and the coarse pulp was subjected to a secondary alkali treatment at a pulp concentration of 20% (the amount of sodium hydroxide was 50kg / t, the reaction temperature was 95℃, and the reaction time was 1h), and the material yield was 85.54%. After the reaction, the dissolution was washed and treated with a medium-consistency disc grinder at a pulp concentration of 10%, and the pulp was ground to a Canadian freeness of about 300 mL CSF to obtain a fine pulp. After the fine pulp was washed, it was used for papermaking, and the tensile strength of the obtained hand sheet was 0.84 kN / m. The raw material without baking treatment had an alkali treatment yield of 80.39%, a tensile strength of 0.84 kN / m, a yield increase of 6.41%, and unchanged strength.

[0049] Example 3

[0050] Poplar is used as raw material, and after being processed by a chipper, it is passed through a wood chip screen to obtain qualified wood chips with a length of 50mm to 100mm, a width of 2.5mm to 10mm, and a thickness of 4.5mm to 6mm. After the wood chips are washed and dehydrated, they are treated with infrared heat at 115℃ for 50min, wherein the material is taken out after each treatment for 10min, stirred evenly, and then sent to an infrared light box. The final heat treatment yield is 102.55%. The obtained material is pre-impregnated with alkali (the pulp after dry heat pretreatment is impregnated with alkali at a pulp concentration of 20% (based on absolute dry pulp), the amount of sodium hydroxide is 30kg / t, the reaction temperature is 95℃, and the reaction time is 1h). The pulp after alkali impregnation is ground to a Canadian freeness of 550mL CSF using a high-concentration disc mill at 20% to obtain a coarse pulp, and the coarse pulp is subjected to a secondary alkali treatment at a pulp concentration of 20% (the amount of sodium hydroxide is 50kg / t, the reaction temperature is 95℃, and the reaction time is 1h), and the material yield is 89.34%. After the reaction, the eluted material was washed and subjected to medium-consistency disc grinding at 10% pulp concentration to a Canadian freeness of about 300 mL CSF to obtain fine pulp. After the fine pulp was washed, it was used for papermaking, and the tensile strength of the obtained hand sheet was 1.21 kN / m. The raw material without hot air drying treatment had an alkali treatment yield of 87.65%, a tensile strength of 1.22 kN / m, a yield increase of 2.21%, and almost no change in strength.

[0051] Example 4

[0052] Green bamboo is used as raw material, and after being processed by a chipper, it is passed through a wood chip screen to obtain qualified wood chips with a length of 50mm-100mm, a width of 2.5mm-10mm, and a thickness of 4.5mm-6mm. After the wood chips are washed and dehydrated, they are baked at 110℃ for 40min, wherein the material is taken out after each treatment for 5min, stirred evenly, and then sent to the oven. The final heat treatment yield is 101.98%. The obtained material is pre-impregnated with alkali (the pulp after dry heat pretreatment is impregnated with alkali at a pulp concentration of 20% (based on absolute dry pulp), the amount of sodium hydroxide is 30kg / t, the reaction temperature is 95℃, and the reaction time is 1h). The pulp after alkali impregnation is ground to a Canadian freeness of 550mL CSF using a high-concentration disc mill at 20% to obtain a coarse pulp, and the coarse pulp is subjected to a secondary alkali treatment at a pulp concentration of 20% (the amount of sodium hydroxide is 50kg / t, the reaction temperature is 95℃, and the reaction time is 1h), and the material yield is 90.76%. After the reaction, the eluted material was washed and subjected to medium-consistency disc grinding at 10% pulp concentration to a Canadian freeness of about 300 mL CSF to obtain fine pulp. After the fine pulp was washed, it was used for papermaking, and the tensile strength of the obtained hand sheet was 0.83 kN / m. The raw material without baking treatment had an alkali treatment yield of 87.82% and a tensile strength of 0.84 kN / m, with a yield increase of 3.35% and almost no change in strength.

[0053] Example 5

[0054] Larch was used as the raw material, and after being processed by a chipper, it was passed through a wood chip screen to obtain qualified wood chips with a length of 50mm-100mm, a width of 2.5mm-10mm, and a thickness of 4.5mm-6mm. After the wood chips were washed and dehydrated, they were dried with hot air at 120℃ for 60min, and the material was taken out every 5min, stirred evenly, and then sent to the hot air box. The final heat treatment yield was 101.30%. The obtained material was pre-impregnated with alkali (the slurry after dry heat pretreatment was alkali impregnated at a pulp concentration of 20% (based on absolute dry pulp), the amount of sodium hydroxide was 30kg / t, the reaction temperature was 95°C, and the reaction time was 1h), and the slurry after alkali impregnation was ground to a Canadian freeness of 550mL CSF using a high-concentration disc mill at 20% to obtain a coarse pulp, and the coarse pulp was subjected to a secondary alkali treatment at a pulp concentration of 20% (the amount of sodium hydroxide was 50kg / t, the reaction temperature was 95°C, and the reaction time was 1h), and the material yield was 85.40%. After the reaction was completed, the dissolution was washed and subjected to a medium-concentration disc mill at a pulp concentration of 10%, and ground to a Canadian freeness of about 300mL CSF to obtain a fine pulp. After the fine pulp was washed, it was paper-made, and the tensile strength of the obtained hand sheet was 1.34kN / m. The raw material that has not been dried with hot air has a yield of 81.83% after alkali treatment, and a tensile strength of 1.34 kN / m. The yield is increased by 4.36%, and the strength remains unchanged.

[0055] The present invention provides a method and idea for improving the alkali impregnation yield of fiber raw materials. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

[0056] Comparative Example 1

[0057] Comparative Example 1 uses green bamboo as raw material, which is processed by a chipper and then passed through a wood chip sieve to obtain qualified wood chips with a length of 50mm to 100mm, a width of 2.5mm to 10mm, and a thickness of 4.5mm to 6mm. After the wood chips are washed and dehydrated, they are treated with a hydrothermal reaction at 130°C for 30min, and the final heat treatment yield is 98.77%. The obtained material is pre-impregnated (the slurry after hydrothermal pretreatment is alkali-impregnated at a pulp concentration of 20% (based on absolute dry pulp, the same below), the amount of sodium hydroxide is 30kg / t, the reaction temperature is 95°C, and the reaction time is 1h). The slurry after alkali impregnation is ground to a Canadian freeness of 550mL CSF using a high-concentration disc mill at 20% to obtain a coarse pulp, and the coarse pulp is subjected to a secondary alkali treatment at a pulp concentration of 20% (the amount of sodium hydroxide is 50kg / t, the reaction temperature is 95°C, and the reaction time is 1h), and the material yield is 87.30%. After the reaction, the eluted material was washed and subjected to medium-consistency disc grinding at 10% pulp concentration to a Canadian freeness of about 300 mL CSF to obtain fine pulp. After the fine pulp was washed, it was used for papermaking, and the tensile strength of the obtained hand sheet was 0.85 kN / m. The raw material without hydrothermal treatment had an alkali treatment yield of 87.82% and a tensile strength of 0.84 kN / m, and the yield and strength were almost unchanged.

[0058] It can be seen that the use of hydrothermal (non-dry heat treatment) method to pretreat the fiber raw materials, because the water content in the system is too high, the heat of the heat treatment is used for water evaporation, which cannot effectively excite free radicals, and thus cannot form a stable connection bond between the precursor small molecules and the fiber raw materials, thereby achieving the purpose of increasing the pulping yield.

[0059] Comparative Example 2

[0060] Comparative Example 3 uses black poplar as raw material, which is processed by a chipper and then passed through a wood chip screen to obtain qualified wood chips with a length of 50mm to 100mm, a width of 2.5mm to 10mm, and a thickness of 4.5mm to 6mm. After the wood chips are washed and dehydrated, they are dried with hot air at 110°C for 5min, and the final heat treatment yield is 99.27%. The obtained material is pre-impregnated (the pulp after hot air drying is alkali-impregnated at a pulp concentration of 20% (based on absolute dry pulp, the same below), the amount of sodium hydroxide is 30kg / t, the reaction temperature is 95°C, and the reaction time is 1h). The pulp after alkali impregnation is ground to a Canadian freeness of 550mL CSF using a high-concentration disc mill at 20% to obtain a coarse pulp, and the coarse pulp is subjected to a secondary alkali treatment at a pulp concentration of 20% (the amount of sodium hydroxide is 50kg / t, the reaction temperature is 95°C, and the reaction time is 1h), and the material yield is 87.01%. After the reaction, the eluted material was washed and subjected to medium-consistency disc grinding at 10% pulp concentration to a Canadian freeness of about 300 mL CSF to obtain fine pulp. After the fine pulp was washed, it was used for papermaking, and the tensile strength of the obtained hand sheet was 1.20 kN / m. The raw material without hydrothermal treatment had an alkali treatment yield of 87.65% and a tensile strength of 1.22 kN / m, and the yield and strength were almost unchanged.

[0061] It can be seen from this that when the treatment time is too short, the lower heat treatment temperature is not enough to provide sufficient energy to the fiber raw material to excite various precursor small molecules into free radicals, so free radical condensation reaction cannot occur, and there is no significant change in pulping yield and paper strength.

Claims

1. A method for improving the alkali impregnation yield of fiber raw materials, characterized in that: After the fiber raw materials are screened to obtain qualified wood chips, the washed and dehydrated fiber raw materials are subjected to at least one dry heat treatment before alkali impregnation, the treatment temperature is 105°C~130°C, and the total treatment time is 10 min~60 min.

2. The method according to claim 1, characterized in that The dry heat treatment is any one or a combination of hot air drying, baking and infrared heat treatment.

3. The method according to claim 1, characterized in that The washed and dehydrated fiber raw materials are subjected to several dry heat treatments. After each treatment for 5 to 8 minutes, the material is taken out and stirred evenly before the next dry heat treatment.

4. The method according to claim 3, characterized in that The fiber raw material is any one or more of eucalyptus, poplar, acacia, pine and bamboo.

5. The method according to claim 3, characterized in that: The steps of alkali impregnation are as follows: alkali impregnation of the dry heat pretreated pulp is carried out based on the condition that the pulp concentration of the absolute dry pulp is 20%, the amount of sodium hydroxide used is 30kg / t absolute dry pulp, the reaction temperature is 95°C, and the reaction time is 1 h.

6. A papermaking method, characterized in that: The steps include: (1) Screening, washing and dehydrating the fiber raw materials; (2) subjecting the raw material obtained in step (1) to at least one dry heat treatment at a temperature of 105°C to 130°C and a total treatment time of 10 min to 60 min; (3) The fiber raw material obtained in step (2) is subjected to an alkali impregnation treatment, wherein the treatment conditions are as follows: the slurry after dry heat pretreatment is subjected to an alkali impregnation at a slurry concentration of 20% based on absolute dry slurry, the amount of sodium hydroxide used is 30 kg / t absolute dry slurry, the reaction temperature is 95° C., and the reaction time is 1 h; (4) The slurry obtained after the alkali impregnation treatment in step (3) is ground to a Canadian freeness of 550 mL CSF using a high-consistency disc mill at 20% to obtain a coarse pulp, and the coarse pulp is subjected to a secondary alkali treatment at a pulp concentration of 20%, with a sodium hydroxide dosage of 50 kg / t, a reaction temperature of 95°C, and a reaction time of 1 h. After the reaction is completed, the dissolution is washed and subjected to a medium-consistency disc mill at a pulp concentration of 10% to grind it to a Canadian freeness of about 300 mL CSF to obtain a fine pulp; (5) After washing the fine pulp obtained in step (4), papermaking is carried out.

7. The papermaking method according to claim 6, characterized in that: In step (2), the dry heat treatment is any one or a combination of hot air drying, baking and infrared heat treatment.

8. The papermaking method according to claim 6, characterized in that: In step (2), the washed and dehydrated fiber raw material is subjected to dry heat treatment several times. After each treatment for 5 min to 8 min, the material is taken out and stirred evenly before the next dry heat treatment.

9. The papermaking method according to claim 6, characterized in that: In step (2), the fiber raw material is any one or more of eucalyptus, poplar, acacia, pine and bamboo.

Citation Information

Patent Citations

  • Method for improving paper pulp bleaching property

    CN101967771A

  • Chemi-mechanical pulp manufacturing technology

    CN104711880A

  • A method for treating a fibrous material and a plant for carrying out the method

    WO1982004271A1

  • A method for the manufacture of chemithermomechanical pulp

    WO1992020855A1